An Evaluation of Visual Reading and Presentation Learning Domain in Turkish Language Curriculum in the 1st-5th Years of Primary School - Akpinar, Burhan (Turkish Education Assoc, 2009)
Due to the increasing effect of visual materials in daily life, visual reading is accepted as one of the basic skills to be acquired in education. As a reflection of this, a new learning domain, named visual reading and presentation was added to Primary School First Level Turkish Curriculum in 2005-2006 educational year. It is expected that this new learning domain will prepare students better for the 21(st) century which seems to be full of images of all sorts. The aim of this study is to determine the efficiency of visual reading and presentation learning domain in application in Turkish classes, based on the views of teachers. For this purpose, a survey was conducted on 550 classroom teachers. Findings obtained from the analyses of the data can be summarized as follows: it is determined in the study that teachers generally welcome learning domain of visual reading and presentation with an exception of a few objectives and they think that it is efficient in application. Furthermore, teachers think that learning domain of visual reading and presentation has positive effects on learning. However, according to teachers, schools lack the necessary materials to fulfill the requirements of this domain.
Keywords: Visual Reading and Presentation; Visual Literacy; Visual Reading and Teachers' Views